Cover Image, Volume 49, Issue 6 - Kim, Taegu; Yun, Tae Sup; Suh, Hyoung Suk (International journal for numerical and analytical methods in geomechanics, 2025)
The cover image is based on the article Can ChatGPT Implement Finite Element Models for Geotechnical Engineering Applications? by Taegu Kim et al., https://doi.org/10.1002/nag.3956.